Residential Area and Income Inequality in Suburban Indonesia - Pitri Yandri (Indonesian Journal of Geography, 2014)
Suburban becomes footing for the population who migrate from rural to urban areas, especially from livingand housing. Similarly, when the population in urban areas assume that the city is no longer comfortable to their live,so the only possible choice for them is moving to suburb. The subsequent impact of the phenomenon is tremendousconstruction of residential areas as a result of the high demand for housing. The problem then is the construction ofresidential areas often neglect the interests of the local neighborhood. Thus, the residential area becomes a kind of modernresidential area in a local neighborhood. Then it widen its impacts of inequality between communities in residentialarea with communities in local neighborhood. This paper presents the finding that contributor of income inequality insuburbs areas in Indonesia comes from a modern residential area. The evidence for the argument is the result of TheilEntropy Index calculation on modern residential area is higher than the traditional residential area, which is respectively0.34 and 0.15.